Shadow prices of greenhouse gas emissions: An application to the Czech dairy production - Kroupova, Zdenka Z.; Cechura, Lukas; Havlikova, Michaela; Halova, Pavlina; Mali, Michal (My University, 2018)
The paper presents an analysis of the shadow prices of the greenhouse gas emissions in the Czech dairy production industry. There is employed the stochastic frontier multiple output distance function with two market outputs and one non-market (undesirable) output – greenhouse gas emissions – as a representation of a negative public good. The results show that shadow prices differ significantly between producers. Moreover, the price is not stable over time. Significant differences can be seen in shadow prices for the greenhouse gas emissions among the researched group of farmers with respect to the degree of intensification. Most noticeably, the higher the intensification, the higher the shadow price. However, no evidence for a significant relationship between the greenhouse gas prices and technical efficiency was found, and not even the development of the greenhouse gas prices and technical efficiency suggested any common patterns.
Keywords: milk multiple output distance function; stochastic frontier analysis (SFA); undesirable output; valuation